Pengaruh Penambahan Serat Terhadap Karakteristik Mekanis Batako - Wibowo, Hartanto; Yoresta, S.T.,M.T., Dr. Eng. Fengky Satria (Journal of Infrastructural in Civil Engineering, 2024)
Indonesia is a country with some point of earthquake that spread almost throughout its territory. Therefore, in making a building, a strong material is needed and can withstand an earthquake. In its development, has emerged various kinds of technology to improve the quality of building materials. One of some technology that can be used is the method of adding fiber to the concrete mixture. This study aims to determine the effect of the addition of palm fiber, coconut fiber, and bendrat on the mechanical characteristics of concrete blocks. A total of 60 concrete brick samples were made with 0.1 additional fiber variations; 0.3; and 0.5% of the total volume of brick. Testing of mechanical properties include testing compressive strength, flexural strength, modulus of elasticity (MOE), stiffness, and brick ductility. The test results show that the addition of fiber as a brick making mixture tends to increase the quality of the mechanical properties of brick. The highest compressive strength is found in bendrat wire concrete (0.5%) which is 27.21 kg/cm2. The highest flexural strength, MOE, and stiffness values were found in coconut fiber fiber brick (0.3%) with the respective value of 1351.25 kg/cm2; 105.85 kg/cm2; and 194.84 kg/cm. The highest ductility value is found in bendrat wire brick (0.3%) which is 1.70 cm.